Relation of Changes in PEF and FEV1 During Salbutamol-Induced Bronchodilation After Methacholine Challenge Test - Leon L. Csonka; Antti Tikkakoski; Liisa Vuotari; Jussi Karjalainen; Lauri Lehtimäki (Pulmonary Medicine)
Asthma diagnosis can be confirmed by observing significant bronchodilator response (BDR) through peak expiratory flow (PEF) at home or forced expiratory volume in 1 s (FEV1) via spirometry in a clinical setting. We aimed to use the administration of salbutamol after a methacholine challenge test as a model of bronchodilation to study how accurately the change in PEF predicts improvement in lung function, as defined by an increase in FEV1. We analyzed 869 adult patients who were administered salbutamol after a methacholine challenge. To compare relative changes in PEF and FEV1 during bronchodilation, we used regression analysis and constructed a Bland and Altman plot. ROC analysis, sensitivity, specificity, positive and negative predictive values, and kappa coefficient assessed how precisely increases in PEF detected a 12% and 0.2-L improvement in FEV1. The average relative increase in FEV1 was significantly greater than that in PEF. The area under the curve in the ROC analysis was 0.844 for PEF change to detect a 12% and 0.2-L increase in FEV1. The kappa values for changes in PEF and FEV1 ranged from fair to moderate. BDR detected by the recommended 15% and 60 L/min cut-off for PEF identified less than half of true positives, while a 10% cut-off correctly identified close to 75% of them. PEF increase is not a reliable measure of BDR in comparison to FEV1 increase, and a 10% improvement in PEF was the least inaccurate cut-off. Substituting the PEF meter with a handheld spirometer should be further investigated for asthma home monitoring.